2022
DOI: 10.1186/s12909-022-03232-x
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative learning in small groups in an online course – a case study

Abstract: Background The ability to learn collaboratively and work in teams is an essential competency in both educational and healthcare settings, and collaborative student activities are acknowledged as being an important part of the pedagogical approach in higher education and teaching. The course that was the focus of this research, a 15-ECTS-credit online course in philosophy of science, ethics, and research methods, was offered online as part of 11 master’s-level health programmes at a university i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…Also, as many as 86% of students stated that group learning activities with group discussions (4-5 people) were meaningful learning activities. This is in line with the study of Haugland et al [77], who found that collaborative learning in small groups can promote in-depth learning. This study also revealed that learners' obstacles in discussing were not knowing discussion partners, not knowing how to start discussions (embarrassed/confused), and not understanding how to give opinions.…”
Section: Group Learning Processsupporting
confidence: 92%
“…Also, as many as 86% of students stated that group learning activities with group discussions (4-5 people) were meaningful learning activities. This is in line with the study of Haugland et al [77], who found that collaborative learning in small groups can promote in-depth learning. This study also revealed that learners' obstacles in discussing were not knowing discussion partners, not knowing how to start discussions (embarrassed/confused), and not understanding how to give opinions.…”
Section: Group Learning Processsupporting
confidence: 92%
“…Students can also be required to turn on the camera and ask questions so teachers can better supervise their students' learning. In terms of testing the teaching effect, teachers can use the online examination function in learning tools to assess students or use group assessment to reward groups with excellent results from benign competition, strengthen the mutual assistance of students in the group, and finally promote students' autonomous learning (Jorunn et al ., 2022). Therefore, while using MOOCs' online teaching platforms, various innovative e-learning methods can be combined to compensate for the shortcomings of MOOCs and ensure effective communication between teaching and learning.…”
Section: Discussionmentioning
confidence: 99%
“…The and Usagawa [22] considers the selection of services for the creation of mathematical tests, without summarizing the results obtained in other disciplines. Haugland et al explore collaborative learning in small groups in an online course in philosophy of science, ethics, and research methods [23].…”
Section: New Trends and Strategies In The Modern Educational Processmentioning
confidence: 99%